Myxoma Which Originated From Anterior Leaflet of Mitral Valve: Case Report - Habib Cakir; Hasan Uncu; Funda Tor; Cudi Candan Okten; Ahmet Cakallioglu; Ibrahim Ozsoyler (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2012)
In this report, we describe a case with myxoma which originated from anterior leaflet of mitral valve was operated in our clinic. A male patient 50 years old was referred to Cardiology Clinic with the complaint of syncope. In transthoracic echocardiography a mass compatible with the myxoma in left atrium. When left atriotomy was made it was seen a myxoma originated from anterior leaflet of mitral valve. Myxoma was excised with pedicule and mitral valve was repaired. Mitral valve replacement with bileaflet mechanic valve was applied because mitral regurgitation was detected in transesophagial echocardiography after cessation of cardiopulmonary bypass. The patient was discharged with oral anticoagulant drug therapy because of control echocardiography was normal findings and myxoma was detected histopathologically. Myxomas originated from valve region were seen very rarely. Valve repair can be possible after resection of valve originated myxomas however valve replacement may be needed for some patients. [Cukurova Med J 2012; 37(1.000): 55-59]